2000
DOI: 10.1076/0927-3948(200009)831-kft141
|View full text |Cite
|
Sign up to set email alerts
|

Behçet's disease in Japan and in Great Britain: a comparative study

Abstract: Behçet's disease (BD) is an important cause of visual morbidity throughout the world, but shows striking differences in racial predilection. Despite important advances in the therapeutic management of acute intraocular inflammation, the long-term impact of these new strategies on visual outcome of BD and their efficacy in different ethnic groups is unknown. A comparative study of patient characteristics, clinical ocular features and inflammatory score, and current therapy was undertaken on all patients fulfill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
1
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 7 publications
3
16
1
1
Order By: Relevance
“…Although the treatment schedules differed and Japanese patients had more active disease, visual results were comparable. 25 Visual acuity was worse than 6/60 in 31% of patients in Japan and 21% of patients in the United Kingdom. 25 428 A. K. Cingu et al…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the treatment schedules differed and Japanese patients had more active disease, visual results were comparable. 25 Visual acuity was worse than 6/60 in 31% of patients in Japan and 21% of patients in the United Kingdom. 25 428 A. K. Cingu et al…”
Section: Discussionmentioning
confidence: 98%
“…24 Muhaya and associates compared Behçet patients seen in Japan and the United Kingdom in a cross-sectional observational study conducted simultaneously at two centers. 25 The duration of ocular disease was around 7 years in both cohorts. Although the treatment schedules differed and Japanese patients had more active disease, visual results were comparable.…”
Section: Discussionmentioning
confidence: 99%
“…11 This dismal statistic has been reduced by modern immunosuppressive agents and more targeted immunomodulators, but up to 15% of ocular patients remain resistant to intervention. 12 Cyclosporine, tacrolimus (FK 506), azathioprine, and anti-T cell monoclonal antibodies have all proved useful in controlling ocular disease in the short term, but their effect over the duration of active eye disease, which may be two to three decades, remains unproved. [13][14][15][16] However, with increasing knowledge of the immune events that underlie Behçet's disease, newer interventions have become more targeted.…”
Section: Ocular Diseasementioning
confidence: 99%
“…The pattern of BU has been well documented in some countries where the disease is endemic [3,[6][7][8][9][10][11][12], and studies have shown similarities and distinct differences in epidemiologic profiles, ocular involvement, complications, and visual prognosis. However, recent data on BU from the North African region are scarce [13,14], and published studies in the English literature are lacking.…”
Section: Introductionmentioning
confidence: 97%